Performance of optical code division multiple access (CDMA) in optical fibre network - Zou, Wei. (2008)
Code division multiple access (CDMA) technology has been applied to optical fibre networks as it allows multiple users to access the network asynchronously, simultaneously, and securely. Being still a research technology, optical CDMA (OCDMA) is expected to be used in future ultrahigh-speed local area networks where the communication bit rate may be more than lOOGb/s. When code sequences with fixed in-phase crosscorrelation are used, a special OCDMA system, which is referred to as spectral-amplitude-coding (SAC-) system, can cancel the effect of multi-user interference (MUI) by using a reference decoder. This thesis has focused on problems in a SAC-OCDMA system and studied them in several aspects.